Meta-transcriptomics for the diversity of tick-borne virus in Nujiang, Yunnan Province - Wang, Juan; Wang, Jing; Kuang, Guopeng; Wu, Weichen; Yang, Lifen; Yang, Weihong; Pan, Hong; Han, Xi; Yang, Tian; Shi, Mang; Feng, Yun (Frontiers in Cellular and Infection Microbiology, 2023)
Ticks, an arthropod known for transmitting various pathogens such as viruses, bacteria, and fungi, pose a perpetual public health concern. A total of 2,570 ticks collected from Nujiang Prefecture in Yunnan Province between 2017 and 2022 were included in the study. In the analysis of these specimens, we identified four locally distributed tick species, among which Rhipicephalus microplus was dominant. Through the meta-transcriptomic sequencing of four locally distributed tick species, we identified 13 RNA viruses belonging to eight viral families, including Phenuiviridae, Nairoviridae, Peribunyaviridae, Flaviviridae, Chuviridae, Rhabdoviridae, Orthomyxviridae, and Totiviridae. The most prevalent viruses were members of the order Bunyavirales, including three of Phenuiviridae, two were classified as Peribunyaviridae, and one was associated with Nairoviridae. However, whether they pose a threat to human health still remains unclear. Indeed, this study revealed the genetic diversity of tick species and tick-borne viruses in Nujiang Prefecture based on COI gene and tick-borne virus research. These data clarified the genetic evolution of some RNA viruses and furthered our understanding of the distribution pattern of tick-borne pathogens, highlighting the importance and necessity of monitoring tick-borne pathogens.